Solid electrolyte and preparation method thereof
By using CeF3 particles with surface coated SiO2 as filler in solid electrolytes, the problem of poor interfacial compatibility between the filler and the polymer phase is solved, the ion conductivity and ion migration number are improved, and the lithium ion transmission efficiency is improved.
Patent Information
- Application Number
- CN202510066014.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Existing solid electrolytes have challenges in improving ion conductivity and interface compatibility, especially due to poor interfacial compatibility between fillers and polymer phases, which affects ion transport efficiency.
CeF3 particles surface-coated SiO2 are used as fillers to interact with fluorine-containing groups in the PVDF-HFP polymer phase, reduce the crystallinity of the polymer segment structure, improve the interface compatibility between the filler phase and the polymer phase, thereby improving the ionic conductivity and ion mobility.
The ion conductivity and ion migration number of solid electrolytes are improved, the interface compatibility between the filler phase and the polymer phase is improved, and the lithium ion transmission efficiency is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a solid electrolyte and a preparation method thereof. Background Art
[0002] Traditional liquid batteries are prone to safety issues during use, and the use of non-fluid solid electrolytes is the future trend. Polymer solid electrolytes are low-cost and easy to process, but have low conductivity. Filler doping is an effective means to improve the ion conductivity of electrolytes, and has made extensive progress, but the compatibility between fillers and polymer phases is poor, which will affect the ion transmission efficiency.
[0003] Therefore, a LATP ceramic particle reinforced quasi-solid polymer electrolyte is proposed in patent CN 117913357 A, which is a preparation method for a composite quasi-solid polymer electrolyte for solid-state lithium metal batteries by adding LATP (lithium aluminum titanium phosphate) ceramic particles to improve the interfacial reaction and increase the ionic conductivity. However, this type of preparation method requires the addition of LATP ceramic particles, and the LATP ceramic particle preparation process has high requirements, and the particle size is difficult to control. Large-sized LATP particles are prone to agglomeration, which affects the ionic conductivity. In addition, the LATP ceramic phase has poor compatibility with the polymer phase, has fewer surface active sites, and there is an ion concentration difference on both sides of the phase boundary. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a solid electrolyte with high ion conductivity and good interface compatibility and a preparation method thereof.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a solid electrolyte, comprising the following steps: preparing a precursor solution using CeF3 particles coated with SiO2 on the surface, LiTFSi (lithium bistrifluoromethanesulfonyl imide), DMF (N,N-dimethylformamide) and PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene copolymer) powder, drying the precursor solution into a film, and obtaining a solid electrolyte.
[0006] Another technical solution adopted by the present invention is: a solid electrolyte is prepared by the above-mentioned method for preparing the solid electrolyte.
[0007] The beneficial effects of the present invention are as follows: the preparation method of the present invention uses PVDF-HFP as a polymer electrolyte matrix, and increases surface active sites by coating SiO2 with a high specific surface area on the surface of the filler CeF3, increases the interaction with the fluorine-containing groups in the polymer phase, reduces the overall crystallinity of the composite polymer electrolyte, increases the ionic conductivity, increases the ion migration number, and improves the interface compatibility between the filler phase and the polymer phase. DETAILED DESCRIPTION
[0008] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in conjunction with the implementation modes.
[0009] A method for preparing a solid electrolyte comprises the following steps: preparing a precursor solution using CeF3 particles coated with SiO2 on the surface, LiTFSi, DMF and PVDF-HFP powder, and drying the precursor solution into a film to obtain a solid electrolyte.
[0010] From the above description, it can be seen that the beneficial effects of the present invention are: the present invention uses CeF3 particles coated with SiO2 on the surface as filler, the filler has a high specific surface area, and the surface of the SiO2 coating layer has abundant active sites, such as hydroxyl groups and silicate groups, which will interact with the fluorine-containing groups in the PVDF-HFP polymer phase, reduce the crystallinity of the polymer chain segment structure, improve the interface compatibility between the filler phase and the polymer phase, and increase the amorphous area to improve the lithium ion transmission efficiency.
[0011] The active sites on the surface of the SiO2 coating layer can adsorb large-volume anion groups in the polymer matrix, limiting the disordered migration of anion groups during the charge and discharge process and increasing the ion migration number.
[0012] The present invention uses LiTFSI as a lithium source, and the conductivity, solubility and quality of the formed SEI film are all better.
[0013] Furthermore, the mass ratio of CeF3 particles coated with SiO2, LiTFSi and 20g PVDF-HFP powder is 3:2.5~3:20.
[0014] Furthermore, the preparation method of CeF3 particles with surface coated SiO2 includes: dispersing CeF3 powder in deionized water, adding a dispersant to make a suspension, then ultrasonically dispersing, heating to 80-100°C, adding Na2SiO3 solution, then centrifuging and aging, and drying to obtain CeF3 particles with surface coated SiO2.
[0015] From the above description, it can be seen that compared with adding SiO2 and CeF3 separately, the particle size uniformity of CeF3 with SiO2 coated on the surface is better, which can improve the uniformity of the material; the particles on the surface of the coating layer can be made smaller, which is beneficial to increase the specific surface area. Compared with SiO2 and CeF3 of the same size, the particles have better dispersion.
[0016] CeF3 particles coated with SiO2 have the following advantages: 1. They have abundant active sites, which can reduce the crystallinity of the polymer segment structure and improve the interfacial compatibility between the filler phase and the polymer phase; 2. CeF3 is a fluorine-containing compound that can form compounds that are conducive to lithium conduction at the SEI interface and improve interfacial compatibility; 3. Due to the extremely strong electronegativity of fluorine, CeF3 can increase the dissociation degree of lithium salts in polymer electrolytes and increase the number of mobile ions.
[0017] Furthermore, the dispersant is a sodium hexafluorometaphosphate solution.
[0018] Furthermore, the addition amount of sodium hexafluorometaphosphate solution is 40-50 g / L.
[0019] From the above description, it can be seen that adding too much dispersant will reduce the performance of the electrolyte, while adding too little dispersant will result in poor electrolyte uniformity.
[0020] Furthermore, the aging time is 110~130min.
[0021] From the above description, it can be seen that aging makes the particle size distribution of CeF3 particles coated with SiO2 on the surface more uniform.
[0022] Furthermore, the drying temperature is 110-130°C.
[0023] Furthermore, the preparation method of CeF3 powder includes: dissolving Ce(NO3)3·6H2O in deionized water, then adding NH4F aqueous solution to react, and after the reaction is completed, centrifuging, washing and drying in sequence to obtain CeF3 powder.
[0024] Furthermore, the mass ratio of Ce(NO3)3·6H2O to NH4F in the NH4F aqueous solution is 40~45:11~12.
[0025] Furthermore, the specific conditions of the reaction are: reacting at 100-120°C.
[0026] The specific steps of drying to obtain CeF3 powder are: drying at 75~85℃ under vacuum environment.
[0027] Another technical solution adopted by the present invention is: a solid electrolyte is prepared by the above-mentioned method for preparing the solid electrolyte.
[0028] It can be seen from the above description that the solid electrolyte of the present invention has high ion conductivity and ion migration number and good interface compatibility.
[0029] Embodiment 1 of the present invention is: a method for preparing a solid electrolyte, the steps are as follows: S1: Use an analytical balance to weigh 11.2g of NH4F and 43.4g of Ce(NO3)3·6H2O, and prepare an NH4F aqueous solution with a concentration of 15wt%; put Ce(NO3)3·6H2O into a beaker filled with 30mL of deionized water and stir for 10min at a speed of 120r / min to obtain a Ce(NO3)3·6H2O aqueous solution; slowly add the NH4F aqueous solution to the stirring Ce(NO3)3·6H2O aqueous solution, continue stirring for 40min, and then transfer to a 100mL reactor for reaction at a reaction temperature of 110℃ and a reaction time of 16h; after the reaction is completed, the product is centrifuged, washed with deionized water and anhydrous ethanol in turn, transferred to a vacuum oven for drying at 80℃ for 8h, and then ground, and passed through 400 and 600 mesh sieves to obtain CeF3 powder.
[0030] S2: CeF3 powder was dispersed in 300mL deionized water, 2mL of 45g / L sodium hexafluorometaphosphate solution was added to make a suspension, and then ultrasonically dispersed for 20min; the mixture after ultrasonic dispersion was placed in a 90°C water bath and stirred at a stirring speed of 120r / min, 250mL of 20g / L Na2SiO3 solution was slowly added during the stirring process, and then centrifuged and aged for 120min, and dried at 120°C for 20h to obtain CeF3 particles with SiO2 coated on the surface.
[0031] S3: Add 3g of CeF3 particles coated with SiO2 and 2.7g of LiTFSi into a beaker containing 50g of DMF and stir evenly. Weigh 20g of PVDF-HFP powder and slowly add it into the beaker under stirring. The stirring speed is 120r / min. Stirring is continued for 8h to obtain a uniform precursor solution. Put it into a vacuum defoamer to remove the gas mixed in during the stirring process. Then use a 2000um scraper to evenly coat the precursor solution on a polytetrafluoroethylene plate. Put it into a vacuum drying oven at 60°C and dry it for 24h to obtain a solid electrolyte.
[0032] Comparative Example 1 of the present invention is: replacing CeF3 particles with SiO2 coated on the surface with CeF3 of equal mass.
[0033] Comparative Example 2 of the present invention is: replacing CeF3 particles with SiO2 coated on the surface with SiO2 of the same mass.
[0034] The following tests were performed on the solid electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2: 1. The ion migration number of the solid electrolyte prepared in Example 1, Comparative Example 1 and Comparative Example 2 was detected by the following method: a symmetrical Li | SSEs | Li battery was assembled, and the lithium ion migration number (tLi +) of the sample film was measured by combining electrochemical impedance spectroscopy (EIS) and direct current (DC) polarization method, which can be calculated according to the following formula:
[0035] Where △V represents the applied polarization voltage (unit: V), which is 10 mV. I0 and R0 represent the initial current and battery interface resistance, respectively. s and R s Respectively represent the current and battery interface resistance in steady state; the test results are shown in Table 1 Table 1
[0036] As can be seen from Table 1, adding CeF3 particles coated with SiO2 on the surface can adsorb large-volume anion groups in the polymer matrix, limit the disordered migration of anion groups during the charge and discharge process, and increase the ion migration number.
[0037] 2. The ionic conductivity of the solid electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2 was tested by assembling symmetrical stainless steel (SS) | SSEs | SS batteries and measuring the ionic conductivity of the electrolytes by electrochemical impedance spectroscopy (EIS). The open circuit voltage was used and the test frequency range was 0.01 Hz to 1000 kHz. The conductivity value can be calculated by the following formula:
[0038] Where σ represents the ionic conductivity of the sample membrane, unit: S·cm -1 ; R, l and S represent the bulk resistance (unit: Ω), thickness (unit: cm) and area (unit: cm) of the measured electrolyte membrane respectively. 2 ). The test results are shown in Table 2.
[0039] Table 2
[0040] It can be seen from Table 1 and Table 2 that the present invention improves the interface compatibility between the filler and the polymer by adding CeF3 particles with SiO2 coated on the surface, provides more ion pathways, and thus improves the ion migration number and ion conductivity.
[0041] Embodiment 2 of the present invention is: a method for preparing a solid electrolyte, the steps are as follows: S1: Use an analytical balance to weigh 11g of NH4F and 40g of Ce(NO3)3·6H2O, and prepare an NH4F aqueous solution with a concentration of 15wt%; put Ce(NO3)3·6H2O into a beaker filled with 30mL of deionized water and stir for 10min at a speed of 120r / min to obtain a Ce(NO3)3·6H2O aqueous solution; slowly add the NH4F aqueous solution into the stirring Ce(NO3)3·6H2O aqueous solution, continue stirring for 40min, and then transfer to a 100mL reactor for reaction at a reaction temperature of 100℃ and a reaction time of 16h; after the reaction is completed, centrifuge the product, wash it with deionized water and anhydrous ethanol in turn, transfer it to a vacuum oven, dry it at 75℃ for 8h, grind it, and pass it through 400 and 600 mesh sieves to obtain CeF3 powder.
[0042] S2: CeF3 powder was dispersed in 300mL deionized water, 2mL of 40g / L sodium hexafluorometaphosphate solution was added to make a suspension, and then ultrasonically dispersed for 20min; the mixture after ultrasonic dispersion was placed in a 90°C water bath and stirred at a stirring speed of 120r / min, 250mL of 20g / L Na2SiO3 solution was slowly added during the stirring process, and then centrifuged and aged for 110min, and dried at 110°C for 20h to obtain CeF3 particles with SiO2 coated on the surface.
[0043] S3: Add 3g of CeF3 particles coated with SiO2 on the surface and 2.5g of LiTFSi into a beaker containing 50g of DMF and stir evenly. Weigh 20g of PVDF-HFP powder and slowly add it into the beaker under stirring. The stirring speed is 120r / min. Stirring is continued for 8h to obtain a uniform precursor solution. Put it into a vacuum defoamer to remove the gas mixed in during the stirring process, and then use a 2000um scraper to evenly coat the precursor solution on a polytetrafluoroethylene plate. Put it into a vacuum drying oven at 60°C and dry it for 24h to obtain a solid electrolyte.
[0044] Embodiment 3 of the present invention is: a method for preparing a solid electrolyte, the steps are as follows: S1: Use an analytical balance to weigh 12g of NH4F and 45g of Ce(NO3)3·6H2O, and prepare an NH4F aqueous solution with a concentration of 15wt%; put Ce(NO3)3·6H2O into a beaker filled with 30mL of deionized water and stir for 10min at a speed of 120r / min to obtain a Ce(NO3)3·6H2O aqueous solution; slowly add the NH4F aqueous solution to the stirring Ce(NO3)3·6H2O aqueous solution, continue stirring for 40min, and then transfer to a 100mL reactor for reaction at a reaction temperature of 120℃ and a reaction time of 16h; after the reaction is completed, centrifuge the product, wash it with deionized water and anhydrous ethanol in turn, transfer it to a vacuum oven and dry it at 85℃ for 8h, then grind it, and pass it through 400 and 600 mesh sieves to obtain CeF3 powder.
[0045] S2: CeF3 powder was dispersed in 300 mL of deionized water, and 2 mL of 50 g / L sodium hexafluorometaphosphate solution was added to make a suspension, and then ultrasonically dispersed for 20 min; the mixture after ultrasonic dispersion was placed in a 90°C water bath and stirred at a stirring speed of 120 r / min. During the stirring process, 250 mL of 20 g / L Na2SiO3 solution was slowly added, and then centrifuged and aged for 130 min, and dried at 130°C for 20 h to obtain CeF3 particles with SiO2 coated on the surface.
[0046] S3: Add 3g of CeF3 particles coated with SiO2 on the surface and 3g of LiTFSi into a beaker containing 50g of DMF and stir evenly. Weigh 20g of PVDF-HFP powder and slowly add it into the beaker under stirring. The stirring speed is 120r / min. Stirring is continued for 8h to obtain a uniform precursor solution. Put it into a vacuum defoamer to remove the gas mixed in during the stirring process. Then use a 2000um scraper to evenly coat the precursor solution on a polytetrafluoroethylene plate. Put it into a vacuum drying oven at 60°C and dry it for 24h to obtain a solid electrolyte.
[0047] Embodiment 4 of the present invention is: a solid electrolyte prepared by the preparation method of embodiment 1.
[0048] In summary, the preparation method of the solid electrolyte provided by the present invention has the following advantages: 1. Using CeF3 particles coated with SiO2 as fillers can increase the active sites interacting with PVDF-HFP, improve the interface compatibility between the filler phase and the polymer phase, and increase the lithium ion transmission efficiency and ion migration number; 2. Using LiTFSI as the lithium source, it has excellent conductivity, solubility and SEI film quality; 3. The solid electrolyte has good uniformity and dispersion.
[0049] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the specification of the present invention, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a solid electrolyte, characterized in that: The following steps are involved: CeF3 particles with SiO2 coated on the surface, LiTFSi, DMF solution and PVDF-HFP powder are used to prepare a precursor solution, and the precursor solution is dried to form a film to obtain a solid electrolyte.
2. The method for preparing a solid electrolyte according to claim 1, characterized in that: The preparation method of CeF3 particles with SiO2 coated on the surface comprises: dispersing CeF3 powder in deionized water, adding a dispersant to prepare a suspension, then performing ultrasonic dispersion, heating to 80-100° C., adding a Na2SiO3 solution, then centrifuging and aging, and drying to obtain CeF3 particles with SiO2 coated on the surface.
3. The method for preparing a solid electrolyte according to claim 2, characterized in that: The dispersant is sodium hexafluorometaphosphate solution.
4. The method for preparing a solid electrolyte according to claim 3, characterized in that: The addition amount of the sodium hexafluorometaphosphate solution is 40-50 g / L.
5. The method for preparing a solid electrolyte according to claim 2, characterized in that: The aging time is 110 to 130 minutes.
6. The method for preparing a solid electrolyte according to claim 2, characterized in that: The drying temperature is 110-130°C.
7. The method for preparing a solid electrolyte according to claim 2, characterized in that: The preparation method of the CeF3 powder comprises: dissolving Ce(NO3)3·6H2O in deionized water, then adding NH4F aqueous solution to react, and after the reaction is completed, centrifuging, washing and drying are performed in sequence to obtain CeF3 powder.
8. The method for preparing a solid electrolyte according to claim 7, characterized in that: The mass ratio of Ce(NO3)3·6H2O to NH4F in the NH4F aqueous solution is 40-45:11-12.
9. The method for preparing a solid electrolyte according to claim 7, characterized in that: The specific conditions of the reaction are: reacting at 100-120°C.
10. A solid electrolyte prepared by the method for preparing a solid electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
Inorganic composite material with core-shell structure as well as preparation and application thereof
CN111129582A
Composite quasi-solid electrolyte, preparation method and total battery
CN111463481A
Preparation method of rare earth metal oxide / polymer electrolyte membrane for solid-state lithium-sulfur battery
CN115566263A
Inorganic-organic composite solid electrolyte lithium battery and preparation method thereof
CN115642296A
Composite solid polymer electrolyte and preparation method thereof
CN117728015A